2022
DOI: 10.3389/fimmu.2022.798583
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the m6A Modification of RNA in the Glioblastoma Microenvironment as Revealed by Single-Cell Analyses

Abstract: PurposeGlioblastoma multiforme (GBM) is a common and aggressive form of brain tumor. The N6-methyladenosine (m6A) mRNA modification plays multiple roles in many biological processes and disease states. However, the relationship between m6A modifications and the tumor microenvironment in GBM remains unclear, especially at the single-cell level.Experimental DesignSingle-cell and bulk RNA-sequencing data were acquired from the GEO and TCGA databases, respectively. We used bioinformatics and statistical tools to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…To explore the molecular mechanisms underlying the dialogue established between Fb/Epi cells and macrophages, we analyzed the significant ligand-receptor pairs of the signals from Fb/Epi cells to macrophages. We identified 5 primary signaling pathways in both zebrafish ( Figure 5A ) and neonatal mice Fb/Epi cells ( Figure 5B ), among which 4 signaling molecules are associated with reparative macrophages, including Csf1 , 57 , 58 Cxcl12 , 59 Angptl4 , 60 and Mdk 61 pathways. In macrophages, we identified expression of Csf1r , 57 Sdc4 , 62 , 63 and Cxcr4 64 as the primary receptors of these signals.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the molecular mechanisms underlying the dialogue established between Fb/Epi cells and macrophages, we analyzed the significant ligand-receptor pairs of the signals from Fb/Epi cells to macrophages. We identified 5 primary signaling pathways in both zebrafish ( Figure 5A ) and neonatal mice Fb/Epi cells ( Figure 5B ), among which 4 signaling molecules are associated with reparative macrophages, including Csf1 , 57 , 58 Cxcl12 , 59 Angptl4 , 60 and Mdk 61 pathways. In macrophages, we identified expression of Csf1r , 57 Sdc4 , 62 , 63 and Cxcr4 64 as the primary receptors of these signals.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported prognostic significance in diffuse glioma for ITGA3 and MAP1LC3A, two autophagy-related genes [13], BCL7A, a protein involved in ATP-dependent chromatin remodeling [17], and lipid metabolism genes [18]. More recently, Yuan et al established a positive association between M 6 A methylation status and glioblastoma stemness, immune checkpoint expression, and promotion of an immunosuppressive environment [19]. Our current study, which focused exclusively on grade 4 diffuse www.aging-us.com 9850 AGING gliomas, the most aggressive primary brain tumors, revealed that a nomogram based on COL22A1, IGFBP2, and MPO expression can reliably evaluate patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that HNRNPA2B1 can promote tumor immunity and anti-tumor. For example, there is a significant positive correlation between HNRNPA2B1 and M1 macrophages in esophageal cancer ( 39 ), and the expression of HNRNPA2B1 is higher in M1 macrophages and T/NK cells than in other cells in glioblastoma ( 53 ). In contrast, other studies have revealed that HNRNPA2B1 inhibits tumor immunity.…”
Section: Discussionmentioning
confidence: 99%